Effect of Motherwort total alkaloids on the prostate hyperplasia mice model of pathological changes of related tissue morphology induced by the fetal urogenital sinus implants - Mingsan Miao; Shuo Tian; Ming Bai; Liling Xiang; Jianlian Gao (Elsevier, 2017)
Aim: The research was to study the effect of Motherwort total alkaloids on the prostate hyperplasia mice model of pathological changes of related tissue morphology. Results: Compared with the model group(MG), Motherwort total alkaloid high, medium dose group(HD, MD) could significantly reduced the pathological changes of the prostate (P < 0.01); Finasteride(FG) and Motherwort total alkaloid low dose group(LD) could significantly reduce the pathological changes of the prostate (P < 0.05); Longbishu capsules(LG), Finasteride, Motherwort total alkaloid medium dose group could significantly reduce the pathological changes of the kidney (P < 0.01); Motherwort total alkaloid low dose group could significantly reduce the pathological changes of the kidney (P < 0.05); Motherwort total alkaloids could improve the pathological changes of the thymus and spleen. Conclusion: Motherwort total alkaloid can improve the pathological changes of prostatic hyperplasia in mice. Keywords: Motherwort total alkaloids, Prostate hyperplasia, Mice model, Prostate, Kidney, Thymus, Spleen